2021
DOI: 10.1186/s12933-021-01325-3
|View full text |Cite
|
Sign up to set email alerts
|

Up and down waves of glycemic control and lower-extremity amputation in diabetes

Abstract: Lower extremity amputations (LEA) are associated with a high mortality and medical expenditure. Diabetes accounts for 45% to 70% of LEA and is one of the most potent risk factors for peripheral artery diseases (PAD). The existence of a link between the recent relaxation of glycemic targets and the resurgence of LEA is suggested from the analysis of adult participants in the National Health and Nutrition Examination Survey (NHANES) between 2010 and 2015, when diabetes-related LEA increased by more than 25% asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“… 60 Lower socioeconomic status, which can barely be altered, is associated with an elevated amputation risk in diabetics. 61 Optimal glucose control and diabetes medication like glucagon‐like peptide‐1 receptor agonists have shown beneficial effects on prevention of limb amputation, 62 , 63 whereas sodium glucose cotransporter 2 inhibitors are suspected of increasing the risk for amputation in PAD patients. 64 , 65 Emphasizing the high value of continuous monitoring, a UK study revealed a significant reduction of amputation rates after improving diabetic foot care.…”
Section: Discussionmentioning
confidence: 99%
“… 60 Lower socioeconomic status, which can barely be altered, is associated with an elevated amputation risk in diabetics. 61 Optimal glucose control and diabetes medication like glucagon‐like peptide‐1 receptor agonists have shown beneficial effects on prevention of limb amputation, 62 , 63 whereas sodium glucose cotransporter 2 inhibitors are suspected of increasing the risk for amputation in PAD patients. 64 , 65 Emphasizing the high value of continuous monitoring, a UK study revealed a significant reduction of amputation rates after improving diabetic foot care.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that intensive blood glucose control may lead to hypoglycemia [44][45][46][47]. Nevertheless, the relaxation of blood glucose control has contributed to the return of LEA based on an analysis of adult participants in the National Health and Nutrition Survey (NHANES) from 2010 to 2015 [48]. The Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial collected 10251 randomly selected type 2 diabetic patients at 77 locations in the United States and Canada.…”
Section: Plos Onementioning
confidence: 99%
“…Diabetes-related complications, including acute myocardial infarctions, strokes and lower extremity amputations, increased by 25% between 2010 and 2015 among young adults (aged 18–44 years) and middle-aged adults (aged 45–64 years) in the USA 1. Accordingly, diabetes is associated with high rates of morbidity and disability due to chronic complications, particularly in the working-age population 1 2. Between 1995 and 2017, Global Burden of Diseases data showed that diabetes moved from seventh to fourth place in Italy in terms of disability-adjusted life years, which represent the number of years lost to disease, disability and premature death 3…”
Section: Introductionmentioning
confidence: 99%